2021
DOI: 10.3389/fonc.2021.668505
|View full text |Cite
|
Sign up to set email alerts
|

Melanotic Neuroectodermal Tumor of Infancy: A Clinicopathological and BRAF V600E Mutation Study of 11 Cases

Abstract: PurposeTo investigate the clinicopathological features and BRAF V600E mutation of melanotic neuroectodermal tumor of infancy (MNTI).Materials and MethodsEleven cases of MNTI diagnosed at the Department of Oral Pathology were collected. Clinicopathological characteristics were obtained from the medical records. Immunostaining was performed by immunohistochemistry (IHC). Amplification-Refractory Mutation System-qPCR (ARMS-qPCR) and Sanger Sequencing were used to detect BRAF V600E mutation.ResultsOf the 11 cases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…More than 500 cases of MNTI have been reported worldwide by Rachidi et al In addition to the 472 cases reported between 1918 and 2013 as a part of the largest retrospective study, [5] we found 49 cases reported between January 2014 and June 2021 by searching PubMed [3,4,9–32,36–38] . In a systematic review of 472 MNTI cases, [5] most cases developed within 1 year of age, with more than 90% of cases occurring in the craniofacial region, such as the maxilla (60.3%), skull (18.1%), and mandible (10.3%).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…More than 500 cases of MNTI have been reported worldwide by Rachidi et al In addition to the 472 cases reported between 1918 and 2013 as a part of the largest retrospective study, [5] we found 49 cases reported between January 2014 and June 2021 by searching PubMed [3,4,9–32,36–38] . In a systematic review of 472 MNTI cases, [5] most cases developed within 1 year of age, with more than 90% of cases occurring in the craniofacial region, such as the maxilla (60.3%), skull (18.1%), and mandible (10.3%).…”
Section: Discussionmentioning
confidence: 75%
“…More than 500 cases of MNTI have been reported worldwide by Rachidi et al In addition to the 472 cases reported between 1918 and 2013 as a part of the largest retrospective study, [ 5 ] we found 49 cases reported between January 2014 and June 2021 by searching PubMed. [ 3 , 4 , 9 32 , 36 38 ] In a systematic review of 472 MNTI cases, [ 5 ] most cases developed within 1 year of age, with more than 90% of cases occurring in the craniofacial region, such as the maxilla (60.3%), skull (18.1%), and mandible (10.3%). On the other hand, to summarize the reported cases since 2014, 27 (87.1%) cases of MNTI developed within 1 year of age, and 32 (65.3%) cases occurred in the maxilla, 4 (8.2%) in the mandible, and 1 (2%) in the hard palate, while 12 (24.5%) cases occurred outside the oral cavity, such as the cranial bone, middle ear, upper arm, fibula, and ovary.…”
Section: Discussionmentioning
confidence: 99%
“…The result is that our case did not harbor BRAFV600E mutation, which is consistent with another study. 17 In addition, Barnes et al reported, in 2016, that a germline mutation of CDKN2A and a novel RPLP1:: C19MC fusion was detected in MNTI. 18 Further research is needed to get a better understanding of molecular biology and warranted to improve the efficiency of current treatment strategies.…”
Section: Discussionmentioning
confidence: 99%